ANALISIS PEMIKIRAN FEMINISME MAYA ANGELOU SEPERTI TERCERMIN DALAM PUISI STILL I RISE, PHENOMENAL WOMAN, DAN EQUALITY - AMALIA, TIARA; WANTASEN, ISNAWATY L.; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  ABSTRACTThe title of this research is â€œAnalisis Pemikiran Feminisme Maya Angelou Seperti Tercermin dalam Puisi Still I Rise, Phenomenal Woman, dan Equalityâ€ which is aimed to discover the black feminist thought in three poems by Maya Angelou through the kinds of figurative language and imagery. This research uses descriptive method in analyzing the data with two steps. The first step is identifying figurative language and imagery in each poems. The second step is analyzing how black feminist thought which is reflected in Maya Angelouâ€™s poems through figurative language and imagery. This research focuses on the analysis of figurative language, the kinds of imagery, and black feminism in Maya Angelouâ€™s poems. The writer uses the theory from Perrine (1969) to analyze the figurative language and imagery in the poems. The writer also uses the theory of black feminism from Collins (2000) to analyze how black feminist thought reflected in Maya Angelouâ€™s poems through figurative language and imagery. The results of this study show that in her poems, Angelou uses some figurative language and imagery; there are simile, hyperbole, metaphor, personification, irony, symbol, visual imagery, auditory imagery, and kinesthetic imagery. The writer concludes that black women in these poems are independent, strong, confident, brave, and outspoken. Â Keywords : Poems, Figurative Language, Imagery, Black Feminism, Maya Angelou